2019
DOI: 10.3847/2041-8213/ab303f
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Impact-induced Ejecta from Granular Targets with Large Inclusions

Abstract: We performed impact experiments to observe patterns in an ejecta curtain with targets consisting of small sand particles and large inclusions comparable to or smaller than the size of the projectiles. The spatial intensity distributions in the ejecta at early stages of crater formation depend on the size of the inclusions. Our numerical simulations of radially spreading particles with different sizes support this result. Based on the results, we proposed a procedure for evaluating the subsurface structures of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 11 publications
(12 reference statements)
3
24
0
Order By: Relevance
“…When the particles in the ejecta curtain are spatially concentrated, the intensity contrast should be high. To evaluate the intensity contrast, we analyzed the images using the same procedure by Kadono et al (2019). We investigated the intensity I within the area of N 0 = 100 × 100 pixels around the center of the ejecta curtain, and the area was fixed at the same position in the ejecta curtain in each image.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the particles in the ejecta curtain are spatially concentrated, the intensity contrast should be high. To evaluate the intensity contrast, we analyzed the images using the same procedure by Kadono et al (2019). We investigated the intensity I within the area of N 0 = 100 × 100 pixels around the center of the ejecta curtain, and the area was fixed at the same position in the ejecta curtain in each image.…”
Section: Resultsmentioning
confidence: 99%
“…1d in Kadono et al (2020b). Kadono et al (2015), Kadono et al (2019), Kadono et al (2020a)] have experimentally investigated the pattern in ejecta curtains in laboratories, using targets of single-size particles (glass beads, 50, 100, and 300 μm, and silica sand, 70 μm) and particles with bimodal size distributions (glass beads, 100 μm + 1 mm, 100 μm + 4 mm). The pattern in the ejecta curtains was significantly different: a mesh-like pattern appeared for targets of single-sized particles, whereas a complex filament pattern extending the entire curtain was observed for targets of particles with a bimodal size distribution.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the patterns may be different. In fact, the recent experiments with the target consisting of two kinds of particles in size (0.1 mm and 1 or 4 mm) mixed at almost the same weight % show that large inclusions disturb excavation flow as obstacles and cause different flow patterns such as drags and spurts, but these patterns are temporary and not periodic (Kadono et al 2019). On the other hand, when the amount of small particles is relatively large, the pattern would become similar to the one observed in our experiments.…”
Section: Dependence Of θC On Impact Conditionsmentioning
confidence: 99%
“…Another strong assumption in our model is that all ejecta particles are of equal size. Kadono et al (2019) reported that a target made of different-sized granules produces ejecta curtains with filament patterns. Extending our analytic model to polydisperse granular targets will be the subject of future work.…”
Section: Validity and Limitations Of The Modelmentioning
confidence: 99%